Minimum 20-year follow-up of a press-fit acetabular cup in cementless total hip replacement in young patients - Lunz, André; Falkenhayn, Moritz von; Jäger, Sebastian; Reiner, Tobias; Merle, Christian; Streit, Marcus R.; Renkawitz, Tobias; Innmann, Moritz Maximilian (Acta orthopaedica, 2023)
Purpose: We aimed to determine the minimum 20-year survival rates of a cementless press-fit cup in young patients.Patients and methods: This is a retrospective, single-center, multi-surgeon cohort study investigating the minimum 20-year clinical and radiological outcome of the first 121 consecutive total hip replacements (THRs) using a cementless, press-fit cup (Allofit, Zimmer, Warsaw, IN, USA) performed between 1999 and 2001. 28-mm metal-on-metal (MoM) and ceramic-on-conventionally not highly crosslinked polyethylene (CoP) bearings were used in 71% and 28%, respectively. Median patient age at surgery was 52 (range 21-60) years. Kaplan-Meier survival analysis was conducted for different endpoints.Results: The 22-year survival rate for the endpoint aseptic cup or inlay revision was 94% (95% confidence interval [CI] 87-96) and 99% (CI 94-100) for aseptic cup loosening. 20 patients (21 THRs; 17%) had died and 5 (5 THRs; 4%) were lost to follow-up. No THR showed evidence of radiographic cup loosening. Osteolysis was observed in 40% of THRs with MoM and 77% with CoP bearings. 88% of THRs with CoP bearings showed significant polyethylene wear.Conclusion: The investigated cementless press-fit cup, which is still in clinical use today, showed excellent long-term survival rates in patients under the age of 60 years at surgery. However, osteolysis due to polyethylene and metal wear was frequently observed and is a matter of concern in the third decade after surgery.